A contact lens promising for non-invasive continuous intraocular pressure monitoring. Issue 9 (11th February 2019) - Pang, Yu; Li, Yuxing; Wang, Xuefeng; Qi, Chenjie; Yang, Yi; Ren, Tian-Ling
Abstract : A contact lens with a Wheatstone bridge circuit can achieve high-performance detection of IOP variation. Abstract : Intraocular pressure (IOP) is the key indicator to assess the risk for and status of glaucoma patients, and medication at high IOP values slows down exacerbation of glaucoma. However, the IOP value is subject to circadian variation and cannot be measured continuously in clinical practice. Herein, we have fabricated a contact lens with a Wheatstone bridge circuit for non-invasive monitoring of IOP. A metal electrode has been used as a strain gauge to measure the weak deformation of the eyeball caused by IOP variation. Tests on a model eye indicate that the contact lens exhibits a high sensitivity of 20 μV mmHg −1 and excellent dynamic cycling performance at different speeds of IOP variation. These results demonstrate that the contact lens sensor is promising for continuous IOP monitoring of glaucoma disease, regardless of the posture and activities of the patient.